PENDAPATAN USAHA PENGOLAHAN ROTAN IRIT DI DESA BUKIT LITI KECAMATAN KAHAYAN TENGAH KABUPATEN PULANG PISAU - Asnah Asnah; Atak Rahen (BUANA SAINS, 2007)
Post harvest technologies are needed to produce godd quality rattan. HoweverBut there are always barriers, especially in costs, skills, and emergency need of stuff, so its harvest is still in wet condition. The aim of this research is to learn costs, revenue, income and efficiency of irit rattan in Bukit Liti Village, Kahayan Tengah district, Pulang Pisau sub Province. The data which has been collected, is tabulated and analyzed with using statistics test analysis of farming, which is matched with research’s target. The result and analysis of this research is presented in tables and discussed with discriptive analysis